Eradicating Criminal Acts of Corruption through the Follow the Asset Approach: A Conceptual Analysis from a Criminal Law Perspective - Hutagalung, Argo Johnnes Parlinggoman; Suhaidi, Suhaidi (Rechtsvinding, 2025)
Corruption is an extraordinary crime that has a broad impact on the national economy, governance, and public trust. Efforts to eradicate corruption have tended to focus on the perpetrator (follow the suspect), thus suboptimally recovering state financial losses. One emerging approach is "follow the asset," a law enforcement strategy that emphasizes tracking, confiscating, and seizing assets resulting from corruption. This article aims to conceptually analyze the "follow the asset" approach from a criminal law perspective and its relevance to eradicating corruption in Indonesia. The research method used is normative legal research with a conceptual and statutory approach. The results indicate that the "follow the asset" approach plays a strategic role in creating a deterrent effect, recovering state losses, and strengthening the objectives of criminal punishment. However, its implementation still faces normative and implementation obstacles, particularly regarding evidence, inter-institutional coordination, and the asset confiscation regime.